Lattice Strain and Defects Analysis in Nanostructured Semiconductor Materials and Devices by High‐Resolution X‐Ray Diffraction: Theoretical and Practical Aspects. Issue 2 (23rd December 2021) - Dolabella, Simone; Borzì, Aurelio; Dommann, Alex; Neels, Antonia
Abstract: The reliability of semiconductor materials with electrical and optical properties are connected to their structures. The elastic strain field and tilt analysis of the crystal lattice, detectable by the variation in position and shape of the diffraction peaks, is used to quantify defects and investigate their mobility. The exploitation of high‐resolution X‐ray diffraction‐based methods for the evaluation of structural defects in semiconductor materials and devices is reviewed. An efficient and non‐destructive characterization is possible for structural parameters such as, lattice strain and tilt, layer composition and thickness, lattice mismatch, and dislocation density. The description of specific experimental diffraction geometries and scanning methods is provided. Today's X‐ray diffraction based methods are evaluated and compared, also with respect to their applicability limits. The goal is to understand the close relationship between lattice strain and structural defects. For different material systems, the appropriate analytical methods are highlighted. Abstract : Nanostructures, such as nanowire systems or epitaxial layers, often exhibit complex geometries. Fabrication processes for obtaining these structures affect the crystal lattice coherence of participating materials. The accumulation of defects and their mobility reduce the reliability of devices in applications. High‐resolution X‐ray diffraction methods are essential for the characterization of semiconductor materials and devices.